Some optical solitons and modulation instability analysis of (3+1)-dimensional nonlinear Schrödinger and coupled nonlinear Helmholtz equations - Alsaud, Huda; Youssoufa, Mati; İnç, Mustafa; Inan, Ibrahim Enam; Bicer, Harun (Springer, 2024)
In this study, we acquired some optical solitons of (3 + 1) dimensional nonlinear Schr & ouml;dinger equation (3DNLSE) and coupled nonlinear Helmholtz equations (CNLHE) by using generalized G ' G \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\left(\frac{{G}<^>{\prime}}{G}\right)$$\end{document} -expansion method (GEM). We are able to derive exponential, trigonometric, and hyperbolic solutions. We notice that Mathematica 11.2 offer the equations for these answers. Aside from that, we display some of the solution's graphic performance. Recently, accurate traveling-wave solutions for nonlinear partial differential equations (NLPDEs) have been acquired using this technique. Through linear stability analysis, we derive an analytical expression for the instability gain and analyze its main characteristics. Finally, we assess the robustness and stability of the solitary waves through numerical simulations and compare the accuracy of the analytical and numerical results. The obtained ultra-short optical solitons can be widely used as a guide for practical applications in telecommunications domain.
Keywords: 3DNLSE; CNLHE; GEM; Optical soliton; Modulation instability